2018
DOI: 10.21776/ub.jkb.2018.030.02.5
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi antara kadar Osteocalcin, HbA1C dan 25(OH)D3 pada Anak dengan Diabetes Melitus Tipe 1

Abstract: Masalah yang terjadi di banyak negara salah satunya adalah Diabetes Melitus tipe 1. Prevalensi DM tipe 1 di Indonesia masih belum jelas. DM tipe 1 disebabkan berkurangnya sekresi insulin akibat kerusakan fungsi sel β pankreas oleh karena respon autoimun. Diabetik osteopati merupakan salah satu komplikasi DM, yaitu peningkatan terjadinya osteoporosis. Penelitian ini bertujuan mencari korelasi antara kadar 25(OH)D3, kontrol glikemik dengan mengukur kadar HbA1c dan osteocalcin , sebagai penanda biokimia struktur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Another study by Indriyani and Adji [17] reported that 18 of 28 children with T1DM had HbA1c more than 9%. Wulandari [18] also reported that 73% of 26 children with T1DM had HbA1c levels more than 7.5%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another study by Indriyani and Adji [17] reported that 18 of 28 children with T1DM had HbA1c more than 9%. Wulandari [18] also reported that 73% of 26 children with T1DM had HbA1c levels more than 7.5%.…”
Section: Discussionmentioning
confidence: 93%
“…Insulin sensitivity can decrease at the beginning of puberty and then retrieve to normal after completing somatic growth and sexual maturation [18,19]. Some studies also revealed that the HbA1c level was significantly higher in female patients [18,20,21]. Possible reason might be due to hormonal factors and psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…It made Indonesia the 5 th country in the world in tuberculosis infection. 4,5 Pulmonary tuberculosis in adults is usually made based on clinical presentation and chest Xray examination and confirmed by acid-fast bacilli found in microscopic examination. 6 On the other hand, diabetes mellitus is a chronic high blood glucose level due to impaired insulin secretion, Jurnal Biomedika dan Kesehatan known as type 1 diabetes, or hampered action of insulin or a combination of both, known as type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…9 There are controversies about whether glycemic control affects negative sputum conversion, where some studies showed that there was no connection between them 10, and many other studies showed the opposite. (4,(11)(12)(13)(14) This study was conducted to determine the effect of glycemic control, which showed by random blood glucose level (RBG), HbA1C and the percentage of blood sugar level decrement, to the negative sputum conversion in diabetic patients with pulmonary tuberculosis. Even though many studies have been performed, this study will try to determine which parameter of the three used showed the best sensitivity and specificity in affecting negative sputum smear conversion.…”
Section: Introductionmentioning
confidence: 99%
“…It made Indonesia the 5 th country in the world in tuberculosis infection. 4,5 Pulmonary tuberculosis in adults is usually made based on clinical presentation and chest Xray examination and confirmed by acid-fast bacilli found in microscopic examination. 6 On the other hand, diabetes mellitus is a chronic high blood glucose level due to impaired insulin secretion, known as type 1 diabetes, or hampered action of insulin or a combination of both, known as type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%